THE INFLUENCE OF PJBL MODEL ON DESCRIPTIVE TEXT WRITING SKILLS IN ELEMENTARY SCHOOLS - Sherlin Amaliah Gunaeni; Widia Nur Jannah; Prabawati Nurhabibah (Universitas Majalengka, 2026)
This study motivated by the low level of descriptive writing skills among fifth-grade students at SDN 2 Kasugengan Lor. The main issues include students’ difficulty in expressing their ideas in writing, particularly when writing descriptive texts, as well as the lack of innovative teaching models in the learning process. This study aims to determine the effect of the Project Based Learning (PjBL) model on descriptive writing skills. The method used is a quantitative approach with a quasi-experimental design of the non-equivalent control group type. The research sample consisted of an experimental group and a control group. Data collection instruments included a questionnaire to assess students’ initial abilities and descriptive text writing test in the form of pre-test and post-test. The results of the data analysis indicate that there is a significant difference in students’ writing abilities between the class using the Project Based Learning (PjBL) model and the class using conventional learning. This is evidenced by the experimental class’s post-test mean score of 85.17, which is higher than the control class’s score of 81.14, along with a significance value of 0.000 (<0. 05). Thus, the Project Based Learning (PjBL) model has been proven effective in improving descriptive text writing skills in Indonesian language instruction at the elementary school level.